Relationship Of Age And Parity With Preeclampsia Incidence In Pregnant Women At dr. M. Yunus Hospital In Bengkulu: Hubungan Usia dan Paritas Dengan Kejadian Preeklampsia Pada Ibu Hamil di Rumah Sakit Dr. M Yunus Bengkulu Tahun 2018 - Fahriani, Metha; Sari, Sefti Fusvita; Ramadhaniati, Yuni (Jurnal Kebidanan Midwiferia, 2020)
In 2017 the number of maternal deaths was 28, consisting of 6 maternal deaths, 10 maternal deaths and 12 puerperal maternal deaths. The purpose of this study is to know the relationship of age and parity with the incidence of preeclampsia in pregnant women at dr. M. Yunus Hospital in Bengkulu year 2018. The type of research used is case control. The population in this study were all pregnant women in dr. M. Yunus Hospital in Bengkulu year 2018. The sampling technique was a case sample using total sampling, namely all pregnant women with preeclampsia and control samples using systematic random sampling technique that is sampling using multiples recorded in the hospital register of dr. M. Yunus Hospital in Bengkulu year 2018. The results of this study there is no relationship between age and the incidence of preeclampsia in pregnant women at RSUD dr. M. Yunus in 2018. With the value of p = 0.424> α = 0.05 and the value of Odds Ratio or Risk Estimate = 1.496 and there is a significant relationship between parity and the incidence of preeclampsia in pregnant women at RSUD dr. M. Yunus Bengkulu in 2018. With the value of p = 0.011 <α = 0.05 with the medium category.It is expected that the results of this study can be a program development and service improvement in reducing the prevalence of preeclampsia.